Effect of Static Magnetic Field on Bone Marrow Cellular Density - Mustafa, Bestoon T.; Yaba, Sardar P.; Ismail, Asaad H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
This study was undertaken to investigate the influence of static magnetic field (SMF) on bone marrow cellular density (BMCD) variation proportionally to bone trabeculae. Female albino Wistar rats exposed with 2.4 ± 0.2 millitesla for 1–4weeks duration continuously versus 1h, 2h, 6h, and 8h/day. Trephine biopsy of femurs bone was examined under optical microscope. Data analyzed with ImageJ software. Results showed that short time exposure per day did not enhance the BMCD compare to high exposure period/day. Six hours/day exposure during 1week increased the marrow cellular density (hypercellularity) significantly (P ≤ 0.05) compares to bone trabeculae. Contrarily, 8h/day exposure reduced the BMCD slightly and significantly (hypocellularity, about 50% reduction) due to 1week and 4weeks exposure duration, respectively. The SMF has associated bone marrow cellularity tendency of rat’s femur.